Integrated 8 Wisdom Compounds Interaction in Multitasking Healing System: Confinement Energy in 4D Frequency Interconnection - Hendry Izaac Elim (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2021)
The total energy in multitasking healing system of herbal medicine is extremely important due to an effective recovery of treated cells or organs in human body. This short communication research reports an exact calculation of the total effective mass involve in multitasking healing system of herbal medicine based on a simple smart model from general physics implemented in organic complex compounds found normally in Maluku/ Halmahera Galoba fruits (Zingiberaceae spp.) such as Amomum spp., Hornstedtia spp., Elim alliacea, Etlinger alba (Blume) A.D. Poulsen, et cetera. The invented results shows that the total mass involved in such multitasking healing system is 24.24% with the total number of on-target atoms of 93 atoms from 382 total atoms. This finding suggests that the healing time of herbal medicines with multitasking healing system shall be slower that that from FDA pharmaceutical approved products which is one target with 100% healing system. The value of strong confinement energy in multitasking healing system of such 8 wisdom compounds in herbal medicine based Galoba fruits is about 4 time larger than its weak confinement energy